Influence of lipid lowering fibrates on P-glycoprotein activity in vitro - Ehrhardt, Manuela; Lindenmaier, Heike; Burhenne, Jürgen; Haefeli, Walter E.; Weiß, Johanna (Biochemical pharmacology, 2004)
Statin/fibrate combinations are frequently used to treat mixed dyslipidemia. However, these combinations may cause life-threatening drug interactions (e.g. rhabdomyolysis) possibly induced by modifications of cytochrome P450 isozyme activities. Some statins are also transported by P-glycoprotein (Pgp) and may act as inhibitors of this drug efflux pump. So far, nothing is known about possible Pgp modulating effects of fibrates. We tested whether gemfibrozil, fenofibrate, fenofibric acid, and bezafibrate inhibit Pgp in vitro using a calcein acetoxymethylester (calcein-AM) uptake assay and confocal laser scanning microscopy with bodipy-verapamil as substrate in L-MDR1 cells, which overexpress human Pgp. In uptake assays in cells with (L-MDR1) and without (LLC-PK1) human Pgp we also investigated whether these compounds are transported by Pgp. Intracellular concentrations were measured by liquid chromatography tandem mass spectrometry. Of the tested fibrates, only fenofibrate increased calcein-AM uptake into cells indicating an inhibition of Pgp mediated transport by this compound. The potency of fenofibrate (mean±SD: 7.1±3.2μM), evaluated by calculating the concentration needed to double baseline fluorescence (f2), was similar to that of simvastatin (5.8±1.5μM), lovastatin (10.1±1.0), and verapamil (4.7±0.8μM). For simvastatin and fenofibrate Pgp inhibition was confirmed with confocal laser scanning microscopy. Fenofibrate, fenofibric acid, gemfibrozil, and bezafibrate showed no difference in the cellular uptake between LLC-PK1 and L-MDR1, indicating that the tested fibrates are not Pgp substrates. In conclusion, this study demonstrates that fenofibrate inhibits Pgp in vitro with a potency similar to simvastatin.